2001
DOI: 10.1063/1.1337940
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon excitation modes in nanowire arrays

Abstract: Electron energy loss spectrometry and energy-filtered transmission electron microscopy reveal characteristic plasmon excitations in both isolated Bi nanowires and an array of Bi nanowires within an Al 2 O 3 matrix. As the average nanowire diameter decreases from 90 to 35 nm, both the volume plasmon energy and peak width increase. In addition, a lower-energy excitation is present in a very localized region at the Bi-Al 2 O 3 interface. These results are discussed in the context of quantum confinement and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Its origin does not arise from quantum confinement because the average diameter of the ZnO nanowire is still larger than its exciton Bohr radius (1.8 nm) [47]. It has been reported that electronic and optical properties of nanomaterials are also influenced by the factors like localized strain, the interface effect and defects [48,49]. However, this kind of ''anomalous'' blue shift may be attributed to surface resonance effect [45].…”
Section: Resultsmentioning
confidence: 92%
“…Its origin does not arise from quantum confinement because the average diameter of the ZnO nanowire is still larger than its exciton Bohr radius (1.8 nm) [47]. It has been reported that electronic and optical properties of nanomaterials are also influenced by the factors like localized strain, the interface effect and defects [48,49]. However, this kind of ''anomalous'' blue shift may be attributed to surface resonance effect [45].…”
Section: Resultsmentioning
confidence: 92%
“…In a scanning transmission electron microscope (STEM), the inelastically scattered electrons lose energy to the metal film (Ritchie, 1957, Blackstock, 1955), giving a detailed map of the excited surface plasmon modes (Nelayah, 2007; Koh, 2011; Sigle, 2009; Sigle, 2010; Nelayah, 2009; Chu, 2009; N'Gom, 2009; Schaffer, 2009; Arslan, 2009; Batson, 1982; Batson, 1985; Eggeman, 2007; Little, 1984; Sarid, 1981; Vincent and Silcox, 1973; Pettit, 1975; Sander, 2001). With the advent of high-resolution electron monochromators, energy resolutions of ~50 meV can be obtained (Brink, 2003) giving high spatial and energy resolution maps for scanned samples.…”
Section: Optical Nanostructure Characterizationmentioning
confidence: 99%
“…Other useful advances made using EELS include determination of plasmon-guided modes in buriedmetal (Sarid, 1981, Vincent and Silcox, 1973), metal-insulator (Pettit et al, 1975), and other patterned/nanoparticle geometries (Sander et al, 2001). Spatial energy maps also give detailed information about hybridized plasmon modes in coupled nanoparticles (Schaffer et al, 2009), nanorods (N'Gom et al, 2009), triangular nanoprisms (Nelayah et al, 2009), and other geometries with very small spatial separation between nanostructures (Sigle et al, 2009).…”
Section: Optical Nanostructure Characterizationmentioning
confidence: 99%
“…Secondly, the softened capsule as well as the molten Bi within (note that the melting temperature of bulk Bi is only 271°C) is drawn out by spooling. is method can produce ultralong single-crystalline Bi nanowires along [111] direction in a conventional hexagonal lattice system with diameter down to 55 nm, as shown in Figure 4(a) [70]. Moreover, the surface oxidization to the nanowires can be avoided since in this process the molten Bi is not air-exposed [41].…”
Section: Template-based Methodmentioning
confidence: 97%
“…e same mechanism was also used to explain the near-IR absorption onset observed for D � 3 nm Bi nanospheres [109], and not for a bismuth powder. e existence of a bandgap widening due to confinement in Bi nanostructures was also discussed from the observation of their EELS spectra in the spectral region of their volume plasmons [52,110,111]. Especially, if the picture of "interband plasmonic" resonances predicted by classical models seems to support qualitatively many experimental results, the existence of quantum confinement effects impacting the UV-Vis-near-IR regions also has to be considered.…”
Section: Quantum Confinementmentioning
confidence: 99%